Alfalfa quality improvement and loss reduction technology advances - Wang, Si-Yi; Yang, Guo-Lin; Jing, Yuan-Yuan; He, Zhen-Nan; Liu, Bin; Sun, Le; Zhang, Yue; Gao, Fengqin (Frontiers in Animal Science, 2025)
Forage is an indispensable feed for livestock, and the world is currently facing an imbalance in the “human-grass-livestock” relationship, with a sharp disparity between grass and livestock fundamentally due to insufficient forage resources. It is urgent to promote the development of a high-quality forage industry. According to Mordor Intelligence, the global alfalfa market is expected to reach 25.6 billion in 2024, with a compound annual growth rate of 6.03%, showing strong growth momentum. Optimizing alfalfa, a high-quality forage material with huge volume in the world, modulation and processing technology, exploring the key technologies of improving quality and reducing loss, reducing cost and increasing efficiency, and increasing its application path in livestock feeding, are the key issues to be solved urgently. This article reviews relevant literature published domestically and internationally. The key technologies for alfalfa storage and processing were summarized, and the nutritional value of high-quality forage and the key factors affecting its effectiveness explored, in order to provide references for production technicians and scientific researchers.